Pengaruh Aromaterapi Bitter Orange Terhadap Nyeri Postpartum Sectio Caesarea di RSUD Panembahan Senopati Bantul - Deasya Dara Savira; Dwi Yati (Jurnal Kesehatan Saelmakers PERDANA, 2022)
Postpartum sectio cesarea pain (pain experienced by a mother after birth delivery) will usually increase on the first postoperative day and will be more painful if the effect of the analgesic disappears. Bitter orange is one among other aromatherapy treatments that can be used to treat pain. This research aims to determine the effect of bitter orange aromatherapy on postpartum sectio caesarea pain. The research method is quantitative that uses a quasi-experimental design with a pre-test and post-test approach without a control group with a bitter orange aromatherapy intervention conducted from June-July 2021. The sampling technique was purposive sampling with a total of 25 postpartum sectio caesarea mothers in the Alamanda 3 Ward at RSUD Panembahan Senopati, Bantul. The pain measuring instrument used was NRS (Numeric Rating Scale). The data analysis used the paired t-test method. The results show that there is a difference in the mean level of pain in postpartum sectio caesarea mothers before and after treated with bitter orange aromatherapy with a mean value of 0.680, standard deviation of 0.476 and p-value of 0.000 (p-value <0.05). There is an effect before and after implementing bitter orange aromatherapy on postpartum sectio caesarea pain in Alamanda 3 Ward RSUD Panembahan Senopati Bantul.